2004
DOI: 10.1016/j.ygcen.2003.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Atlantic salmon (Salmo salar) at elevated temperature inhibits cytochrome P450 aromatase activity in isolated ovarian follicles

Abstract: Atlantic salmon (Salmo salar) broodstock were transferred from natural (12-16 o C) to controlled temperatures of 14, 18 or 22 o C for 3 months during vitellogenesis. Fertility and survival were significantly reduced in eggs from broodstock held at 22 o C relative to 14 or 18 o C. Endocrine mechanisms were disrupted after only one month at 22 o C, as evidenced by decreased plasma vitellogenin (Vtg) and increased plasma testosterone (T) levels and, at later stages, decreased levels of plasma 17β-estradiol (E 2 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
28
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 34 publications
14
28
0
Order By: Relevance
“…If a significant temperature-time interaction effect was observed, different letters mean significant (P \ 0.05) differences between temperatures within a given sampling time follicles observed from January. In the Atlantic salmon Salmo salar, elevated temperatures impaired maturation, ovulation and subsequent fertility in females through the disruption of endocrine processes as shown by the altered levels of plasma 17b-estradiol, vitellogenin and testosterone (King et al 2003;Pankhurst and King 2010;Watts et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…If a significant temperature-time interaction effect was observed, different letters mean significant (P \ 0.05) differences between temperatures within a given sampling time follicles observed from January. In the Atlantic salmon Salmo salar, elevated temperatures impaired maturation, ovulation and subsequent fertility in females through the disruption of endocrine processes as shown by the altered levels of plasma 17b-estradiol, vitellogenin and testosterone (King et al 2003;Pankhurst and King 2010;Watts et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that, under elevated temperatures, the enzyme CYP19 aromatase, which catalyzes the irreversible conversion of testosterone into E 2 , is inhibited (Watts et al 2004). First, elevated temperature resulted in a decrease in E 2 concentrations.…”
Section: Hormonal and Physiological Impactsmentioning
confidence: 99%
“…This included examining temperature effects in relation to photothermal conditioning protocols for producing offspring out of season (Morrison and Smith 1986;Johnston et al 1992;Davies and Bromage 2002;Clark et al 2005;Van der Meeren and Ivannikov 2006), concerns for broodstocks at facilities in geographical locations with elevated ambient thermal profiles (Pankhurst et al 1996;Webb et al 1999Webb et al , 2001Watts et al 2004;Brown et al 2006;Pornsoping et al 2007) and strategies to mitigate temperature stress in broodstock (Dzikowski et al 2001;King and Pankhurst 2004b;Vikingstad et al 2008). Conversely, fewer studies were conducted to address temperature exposures in fish within an ecological or conservation context (Buckley et al 1990;Bonner et al 1998;Ouellet et al 2001;St Mary et al 2001;Hilder and Pankhurst 2003;Ito et al 2008).…”
Section: Trends Within the Adult Thermal Holding Studiesmentioning
confidence: 99%
“…Temperature can also act directly at the level of the oocyte. High temperatures have been shown to disrupt processes involved in final oocyte maturation (FOM) and inhibit ovulation in many individuals (Pankhurst et al 1996;Webb et al 2001;Watts et al 2004). Failure of adults to spawn as a result of experiencing suboptimal temperatures could alter the conspecific density of the surviving offspring.…”
Section: Introductionmentioning
confidence: 99%